Long-term costs of dental care for Thailand preschool children by using a system dynamics model - Songchai Thitasomakul; Sukanya Tianviwat; Tin Htet Oo; Phongpat Sontamino (BMC, 2024)
Abstract Background A System Dynamics Model (SDM) is a computer simulation to alleviate the problem by comparing strategies and policies. Addressing the costs by using SDM helps in allocating the resources efficiently in managing the strategies. Objective To describe the costs of primary, secondary, and tertiary prevention of dental caries for 0-5-year-old children by SDM. Methods The SDM was developed to explore the cost of primary and secondary prevention (supervised toothbrushing, STB and fluoride varnish, FV), the treatment cost for caries (tertiary prevention), and the total cost under three scenarios; STB, FV and base case (no intervention). Results When the children aged 5 years, the treatment cost under the base case was the highest at 57.6 million baht while 53.5 million baht in FV and 51.9 million baht in STB. As a total cost, 64.1 million baht under FV, 60.9 million baht under STB, and 57.6 million baht under base case. Sensitivity analysis reveals that the effective rate of STB must be at least 30%, and FV should be a minimum of 50% to ascertain the total cost reduction relative to the base case scenario. Conclusion Caries treatment costs were lower when STB and FV were implemented than in the base case scenario. The overall cost under FV was the highest, followed by STB, with no total cost savings observed as compared to the base case situation. Despite that, carrying out the STB rather than the FV would save a total of 3.2 million baht. Treatment costs under interventions would be lower than expected, and overall cost reductions might be obtained by comparing the base case if the intervention's effective rates are higher, according to sensitivity analysis.